Demonstration (web-based) of cryptographic hashing - Lim, Tony Dong Li (2018)
Rising cybercrimes rates have greatly increased the costs of recovery from cyber-attacks. Therefore, cybersecurity has become a very important area of expertise. Cryptography is one of the key aspects of cybersecurity, therefore, it is a required knowledge for anyone learning cybersecurity. An important concept to understand in cryptography is cryptographic hashing, which are used widely across the cyber world. Cryptographic hashing involves a lot of mathematical concepts and manipulations, which makes it difficult to learn and visualize. With the help of technology, the efficiency of the learning process is greatly increased. Existing simulators, which teaches other cryptographic hashing algorithms, have been effective in aiding the learning process. The reason is that simulators explains the concepts in detailed steps with visual aids and allows user interactions to explore the hashing process. To aid in the learning of the cryptographic hashing concepts, a web-based cryptographic hashing simulator is developed which supports multi-platforms. The focus of this simulator is to make it easier for NTU students taking the course CZ/CE4024 Cryptography and Network Security to learn cryptographic hashing by aiding them in visualizing the hashing algorithm. In this report, various cryptographic hashing algorithms will be explored and the implementation of the simulator for SHA-512 and MD5 using JavaScript will be explained.